2018
DOI: 10.1007/s00262-018-2219-8
|View full text |Cite
|
Sign up to set email alerts
|

Older melanoma patients aged 75 and above retain responsiveness to anti-PD1 therapy: results of a retrospective single-institution cohort study

Abstract: Our study suggests that immunotherapy is effective and well tolerated in the elderly. The PFS on pembrolizumab was greater than expected, a finding that needs to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…A small French study looking at age used a different cut-point, reporting better OS and PFS for 38 patients >65 years (vs 54 patients ≤65) with metastatic melanoma treated with ipilimumab, nivolumab, or pembrolizumab, [41] and a non-comparative single-center study reported that immunotherapy was effective and well-tolerated by older patients (n = 99; all >75 years). [42] Common immune-related adverse effects were similar in different age groups in prior studies, suggesting that older patients can safely tolerate PD-1/PD-L1 inhibitors, [32,41] nonetheless, more studies are needed in future to examine the associations between age and the effectiveness and safety of immunotherapy.…”
Section: Discussionmentioning
confidence: 90%
“…A small French study looking at age used a different cut-point, reporting better OS and PFS for 38 patients >65 years (vs 54 patients ≤65) with metastatic melanoma treated with ipilimumab, nivolumab, or pembrolizumab, [41] and a non-comparative single-center study reported that immunotherapy was effective and well-tolerated by older patients (n = 99; all >75 years). [42] Common immune-related adverse effects were similar in different age groups in prior studies, suggesting that older patients can safely tolerate PD-1/PD-L1 inhibitors, [32,41] nonetheless, more studies are needed in future to examine the associations between age and the effectiveness and safety of immunotherapy.…”
Section: Discussionmentioning
confidence: 90%
“…by anti-PD-1 for metastatic melanoma including 24,5% with serious AEs with pembrolizumab, and 62,5% of patients treated by nivolumab (but with only eight patients treated by nivolumab in this study) [6].…”
Section: Baseline Characteristicsmentioning
confidence: 62%
“…Compared to the study of Muzet et al, OS was 10.1 months and PFS 4.8 months for patients ≥65 years, and this was significantly better for older patients [8]. In a recent retrospective cohort of patients aged over 75 years old treated by immunotherapy for metastatic melanoma, median PFS on pembrolizumab, nivolumab or ipilimumab were equal to 11.9 (95% CI 5.4-18.4), 1.4 (95% CI 0.01-2.8), and 2.8 months (95% CI 2.6-3), respectively, while median OS was not reached in patients who received only pembrolizumab, 8.7 months in the ipilimumab only group, and 23 months in patients receiving several immune therapies sequentially [6]. A meta-analysis also suggested a better benefit for ipilimumab therapy in older adults than younger patients [9].…”
Section: Baseline Characteristicsmentioning
confidence: 95%
“…What could be the consequences for the daily management of elderly patients according to primary tumors? For melanoma patients, Checkmate 066 study and additional cohort studies of patients aged over 80 have confirmed the benefit of ICIs (23,24). The only issue is to consider or not the addition of an anti-CTLA-4 agent according to the geriatric assessment.…”
Section: Discussionmentioning
confidence: 99%